Inheritance Law Reform and Women’s Access to Capital : Evidence from India’s Hindu Succession Act - Deininger, Klaus; Goyal, Aparajita; Nagarajan, Hari (2012)
This paper examines whether and to what extent amendments in inheritance legislation impact women's physical and human capital investments, using disaggregated household level data from India. The authors use inheritance patterns over three generations of individuals to assess the impact of changes in the Hindu Succession Act that grant daughters equal coparcenary birth rights in joint family property that were denied to daughters in the past. The causal effect is isolated by exploiting the variation in the timing of father's death to compare within household bequests of land given to sons and daughters in the states of Maharashtra and Karnataka. The analysis shows that the amendment significantly increased daughters' likelihood to inherit land, but that even after the amendment substantial bias persists. The results also indicate a robust increase in educational attainment of daughters, suggesting an alternative channel of wealth transfer.